Pengaruh Karboksimetil Kitosan Terhadap Aktivitas Antibakteri Staphylococcus aureus pada Sate Bandeng Selama Penyimpanan Suhu Rendah - Fara Wibawa; Nilam Sari; Tasqia Siti Nurul Samsa Hadi; Sakinah Haryati (Faculty of Science and Technology University Ibrahimy, 2023)
Milkfish satay is one of the signature dishes from the Banten Province that tends to experience a rapid decline in quality. Milkfish satay can only stay fresh for approximately 2 days at room temperature and 6 days when stored in cold conditions. This limited shelf life is due to its high nutritional content and various environmental factors. Therefore, a preservative such as carboxymethyl chitosan (CMC) is needed to extend the shelf life of milkfish satay. The objective of this research is to determine the optimal concentration of CMC that is effective as an antibacterial agent for milkfish satay against Staphylococcus aureus bacteria during cold storage. This study employs an experimental method with a Completely Randomized Factorial Design (CRFD) involving two factors and conducted with two replications. The first factor involves four levels of CMC concentration, namely 0%, 3%, 4%, and 5%. Meanwhile, the second factor encompasses six different storage periods, namely day 0, 3, 6, 9, 12, and 15. The parameters tested include antibacterial activity against Staphylococcus aureus, Total Plate Count (TPC), and proximate analysis of the best treatment. It is important to note that the milkfish satay samples used in this research do not represent all milkfish satay from the Banten Province. The samples were obtained from one of the Micro, Small, and Medium Enterprises (MSMEs) with sanitation compliance not meeting the Standard Operating Procedures (SOP). The research results are presented in tabular form and described descriptively. The findings of the study indicate that the addition of carboxymethyl chitosan (CMC) has an impact on the antibacterial activity of milkfish satay, with the optimal CMC concentration being at 5%.